Smart Sensor-GSM Framework for Precise Pollution Localization in Drinking Water Distribution Networks (ELEKTRIKA- Journal of Electrical Engineering, 2025)
In recent years, Baghdad's drinking water quality has been declining, primarily due to untreated sewage, hospital waste, and agricultural runoff being indiscriminately dumped into the Tigris River. The contamination imposes significant health risks to the population. It requires an inexpensive and responsive system that can test water safety at the point of consumption. This research introduces a Smart Sensor-GSM-based framework to oversee water quality in Baghdad's residential distribution network. Utilizing an Arduino Uno microcontroller paired with a GSM module, the system gathers and transmits data from sensors installed on domestic water taps in several districts. These sensors record electrical conductivity (EC) and temperature, which are used to estimate total dissolved solids (TDS). When TDS levels surpass the recommended limit of 500 ppm, in line with WHO and EPA standards, an alert message is automatically dispatched to the monitoring center via SMS. The experiment's water samples collected from six different Baghdad locations recorded TDS values ranging from 200 ppm to 275 ppm, all within safety limits. Calibration tests also confirmed the accuracy of the sensor-based measurements. These findings demonstrate the viability and credibility of the system suggested as a local real-time water quality monitoring system with a viable alternative to traditional laboratory testing.
Keywords: Drinking Water Pollution; Electrical Conductivity; GSM_ GPRS SIM900A; Total Dissolved Solids; Water Quality Monitoring